2020
DOI: 10.3390/jmse8020141
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation on Model- and Full-Scale Marine Propellers: Steady And Transient Viscous Flow Simulations At Different Reynolds Numbers

Abstract: In this paper, we conducted numerical simulations to investigate single and two-phase flows around marine propellers in open-water conditions at different Reynolds number regimes. The simulations were carried out using a homogeneous compressible two-phase flow model with RANS and hybrid RANS/LES turbulence modeling approaches. Transition was accounted for in the model-scale simulations by employing an LCTM transition model. In model scale, also an anisotropic RANS model was utilized. We investigated two types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Shin et al (2018) [17] studied an adaptive grid refinement based on Q-criterion and showed a remarkable improvement in the capturing of tip vortex cavitation. Viitanen et al (2020) [18] also exhibited the significant grid resolution dependency of tip vortex cavitation for an open water propeller. This section discusses the grid sensitivity of the present numerical approach.…”
Section: Resultsmentioning
confidence: 92%
“…Shin et al (2018) [17] studied an adaptive grid refinement based on Q-criterion and showed a remarkable improvement in the capturing of tip vortex cavitation. Viitanen et al (2020) [18] also exhibited the significant grid resolution dependency of tip vortex cavitation for an open water propeller. This section discusses the grid sensitivity of the present numerical approach.…”
Section: Resultsmentioning
confidence: 92%
“…Recently we have investigated the Reynolds number sensitiveness of different cavitation types observed on a ship's propeller [31]. For the case of static hydrofoils exhibiting similar phenomena as shown here, this remains to be assessed.…”
Section: Discussionmentioning
confidence: 94%
“…Usually, the mass-transfer rate is proportional to a pressure difference from a saturated state or to a square root of that. In this study, we employ a mass-transfer model that is similar to that of Choi and Merkle [30], described in [24,31]. The empirical parameters of the cavitation model are calibrated by Sipilä [3].…”
Section: Mass and Energy Transfermentioning
confidence: 99%
“…Even though the calibration was effective for two dimensional case, when employed for three-dimensional propeller analysis, the model overpredicted sheet cavitation and struggled with a cavitation rope vortex. Recently, a study by Viitanen et al [11] confirmed the observations noted in [8]; despite different models, cavitation rope prediction is heavily influenced by grid refinements which minimize dissipation and thus conserve the rope. Zwart and Kunz models, unlike Schnerr-Sauer, utilize empirical constants; hence, their accuracy and applicability heavily depend on the values employed for a case in question.…”
Section: Introductionmentioning
confidence: 80%